The interest rate and the growth rate: Steady-state-efficiency in OLG-models - Ulrich van Suntum (Westfälische Wilhelms-Universität Münster, Centrum für Angewandte Wirtschaftsforschung (CAWM), 2008)
A general model of intertemporal consumption choice is developed, following Samuelson`s 1958 OLG-approach. The efficiency properties of the model are discussed with and without the introduction of durable goods, of productive capital, and fiat money. It is shown that the criterion of golden rule efficiency is not reasonable, if transition periods are taken into account. Moreover, the introduction of an infinitely lived institution, which grows at the steady state rate, will definitely prevent the interest from falling beyond the growth rate. Hence, the main arguments against intertemporal efficiency of the market mechanism in OLG-models turn out to be invalid.
Keywords: 330